Using screws from glycosyled lactic acid (PLGA) in the treatment of calcaneus fractures - S. A. Linnik; A. A. Shuginov; A. V. Nikitin; V. V. Usikov; K. V. Filippov; I. O. Kucheev; Y. B. Tsololo; I. I. Russu; M. G. Kvinikadze (Вестник хирургии имени И.И. Грекова)
Introduction. Heel bone fractures account for about 3 % of the total number of fractures. Various methods of surgical treatment were used depending on the features of a fracture, the condition of soft tissues in a damage area, the general condition of a patient and co-morbidity.The objective was to improve the results of treatment of heel bone fracture by using screws made of glycosylated lactic acid.Methods and materials. The examination and treatment methods as well as the results of surgical treatment of 89 patients diagnosed with a heel bone fracture were analysed. Depending on the type of fractures, all the patients were divided into 4 groups according to Sanders.Results. We studied the short-term (100 %) and long-term (82.5 %) results of treatment of patients using the point-based assessment systems - the Foot Function Index (FFI) scale, and the Clinical rating system for the Ankle and Hindfoot scale.Conclusion. The current study showed that the use of bioimplants along with classical osteosynthesis is one of the advanced technologies in traumatology and orthopedics, which allows to expand the possibilities of surgical fixation of heel bone fractures.